Professionalism and Work Experience on Job Satisfaction and Auditor Performance - Badaruddin Badaruddin; Surianto Surianto; Fatmasari Fatmasari (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine and analyze the impact of professionalism and work experience on auditors' job satisfaction and its implications for their performance at public accounting firms in Makassar. This research employs a survey method to collect data by distributing questionnaires and reviewing documentation. This study's population consisted of 50 auditors, but only 38 participants were sampled. Utilizing Smart PLS 3.0 Software, multiple linear regression analysis is used to analyze the data. The results indicated that experience and professionalism had a positive and statistically significant effect on auditors' job satisfaction. The variable work experience has a positive and statistically significant effect on auditor performance. In the meantime, professionalism has a negative and significant impact on auditor performance; and there is a positive relationship between job satisfaction and auditor performance.